Право на захист персональних даних як нове фундаментальне право людини в інформаційному суспільстві - Сухорольський, Петро Михайлович (Wydawnictwo Uniwersytetu Marii Curie-Skłodowskiej, 2018)
The evolution of data protection law in various legal systems is а conspicuous sign of the influence of technological development on the sphere of human relations. Still, there is no global international convention or other legally binding agreement on the universal level concerning this issue. In such circumstances, it is particularly important to justify the need for global recognition of the right to the protection of personal data as one of the fundamental rights of human being. For this, it is necessary to determine the peculiarities of the right to personal data protection taking into account the current state of technological development and to characterize its main objectives, namely: ensuring transparency, fair distribution of power within and among societies, and possibility for developing its own identity for every person.
Right to the protection of personal data as а new fundamental human right in information society
Keywords: захист персональних даних; права людини; балансування інтересів; право на приватність; інформаційне суспільство